Incorporating floodplain inundation as a strategy in flood mitigation plan - Mah, D.Y.S.; Bustami, R.; Putuhena, F.J. (Universiti Malaysia Sarawak (UNIMAS), 2012)
This paper is promoting the awareness that nature and engineering structure can co-exist together. Natural floodplain inundation is usually restrained to separate floodplain lands for human uses. In contrary to conventional flood control systems, a vision of restoring floodplain inundation in Kuching Bypass Floodway is presented as a flood mitigation plan. Modelling of the approach indicates a reduction of flooded areas up to 61%. By means of modelling, portions of floodplains are virtually preserved in their natural states and functions, a role that often has been undervalued. Floodplain permits storage and conveyance of floodwaters. At the same time, it provides replenishment of the adjoining wetlands. The strategy proves beneficial to both human and natural systems. It also calls for a systemic change in flood management that we can live with the natural forces instead of forbidding them.